(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2022)
Pasemah is located in Sumatra Island. The region’s geography is commonly mountainous, well known as Pasemah Plateau. There are lots of ancient megalith artifacts there, the medium of which is monolithic-andesitic rocks. The artifacts have been investigated since the era of East Indie and are proceeding till now, but the investigations have been archeological in nature. Thus far, there has been no an in-depth study of the artifacts by using a fine arts study like one that the author conducted in the present research. By library study and supplemented by field observation, it could be found out that the existence of the ancient monuments are connected to their surroundings. The megalith artifacts are visual arts works produced creatively in the time, particularly the statues the beginning of which is strongly supposed to serve as the monuments of existence and then turned to be the media of ancestor spirits worship.